Estudios eidéticos. Una conversación desde el Sur sobre la vida de las ideas y la reconfiguración de un espacio disciplinar - Kozel, Andrés (Ariadna Ediciones, 2018)
One of the central novelties that is introduced in this book is the notion of eidetic studies, finally decanted as Title of the work. A good part of the conversations revolve in to specify what this proposal consists of, how to relates to preexisting traditions, in what it looks like and how is it different from other approaches more or less related, how do you think your links with others disciplines It is important to clarify from now that the notion of Eidetic studies is offered both to characterize what has happened and happens in this field of studies as to influence discussions about what you want there happen